TRANSFORMASI KEPEMIMPINAN KIAI BERBASIS SERVANT LEADERSHIP : STRATEGI MEMBANGUN SOLIDARITAS DAN TIME WORK SANTRI - Badrul Mudarris; Jazilurrahman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This article aims to describe and provide a deeper understanding of the Transformation of Kiai Leadership Based on Servant Leadership: A Strategy for Building Students’ Solidarity and Teamwork. To obtain research data, a qualitative approach with a case study method was employed. The study was conducted at Pondok Pesantren Subulus Salam Pajarakan Probolinggo from June to September 2025. Data collection techniques included participant observation, in-depth interviews, and documentation. Meanwhile, data analysis followed the Miles and Huberman model, which consists of data collection, data reduction, data display, and conclusion drawing. The research findings indicate that Transformation of Kiai Leadership Based on Servant Leadership: A Strategy for Building Students’ Solidarity and Teamwork at Pondok Pesantren Subulus Salam Pajarakan Probolinggo is implemented through transformative leadership, collective leadership, competence in Islamic religious education, spiritual guidance, and the exemplary role model of the kiai.